How do patients, medical assistants and physicians accept and experience tablet-based cognitive testing by medical assistants in general practice? - A qualitative study - Kristin Rolke; Carolin Rosendahl; Klaus Weckbecker; Alexander Hanke; Michael Wagner; Leon Nissen; Lara Marie Reimer; Stephan Jonas; Philipp Schaper; Jochen René Thyrian; Florian Schweizer; Judith Tillmann (BMC Primary Care)
Abstract Background Approximately 1.8 million people with dementia live in Germany and the number is expected to increase in the coming years. Between 360,000 and 440,000 new cases are diagnosed each year. General practitioners (GPs) are often the first point of contact for people with concerns about their memory performance or already noticed symptoms of dementia. However, structural barriers can hinder timely diagnosis by GPs, resulting in diagnoses frequently being made later in the disease’s progression. Tablet-based cognitive testing, carried out by medical assistants (MAs) in GP practices, is being tested in the iCreate feasibility study, and could facilitate detection of dementia, allowing those affected to receive timely treatment and support. However, the acceptance, user experience and perceived benefits and consequences of routine implementation of such a not established procedure remain unclear until now. Methods In this qualitative study, seven GPs, six MAs and eight patients were qualitatively interviewed regarding the acceptance, user experience of the tablet-based procedure and its implications for GP care. Semi-structured interviews were conducted using newly developed guidelines, recorded, transcribed and analysed according to Kuckartz and Rädiker using MAXQDA. Results All respondent groups had a positive perception of the digital testing in GP practices. Interviewed MAs welcomed the new responsibilities, and patients gladly accepted the opportunity of cognitive assessment in response to their memory concerns. GPs supported delegating additional tasks to MAs. Patients found the digital testing tasks feasible to complete on the tablet and MAs also had positive experiences using the tablet as test administrators. All groups can generally envision a long-term implementation of the tests in practice, but also noted possible barriers, like the need for additional communication with specialists, limited time resources, and currently insufficient remuneration of cognitive testing. Conclusions The positive user experience and high acceptance of participants indicate that tablet-based cognitive testing in GP settings can be highly feasible and can thus lead to indicated specialist referrals. Consequently, the management of patients exhibiting dementia symptoms should increasingly commence in GP practices, receive adequate funding, and occur in close collaboration with other specialized disciplines.